2020
DOI: 10.18502/kss.v4i9.7318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Destination Image and Subjective Norm toward Intention to Visit the World Best Halal Tourism Destination of Lombok Island in Indonesia

Abstract: One of the halal attractions in Indonesia is Lombok Island, which was ranked as the Best Halal Travel Destination in Indonesia according to the IMTI 2018 and was also named the best halal destination in the international arena in tourism, at the World Halal Travel Summit 2015. In fact, Lombok managed to win two titles at once, namely as the World’s Best Honeymoon Destination and the World’s Best Halal Tourism Destination. Besides being known as the island of 1000 mosques, Lombok also provides easy access to bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 5 publications
0
8
1
8
Order By: Relevance
“…al., 2019) Subsequently, other influential factors are religious belief, infrastructure, halal marketing, halal awareness, and destination image. The results of this research bear different results from previous studies, where the most determining factor of travel intention has been halal marketing (Awan & Nabeel, 2015;Battour, 2018;(Devi & Firmansyah, 2019;Ramadhani et. al., (2020).…”
Section: Saturated Modelcontrasting
confidence: 99%
See 1 more Smart Citation
“…al., 2019) Subsequently, other influential factors are religious belief, infrastructure, halal marketing, halal awareness, and destination image. The results of this research bear different results from previous studies, where the most determining factor of travel intention has been halal marketing (Awan & Nabeel, 2015;Battour, 2018;(Devi & Firmansyah, 2019;Ramadhani et. al., (2020).…”
Section: Saturated Modelcontrasting
confidence: 99%
“…Further Ramadhani et. al., (2020) found that destination image and subjective norms had a significant influence on intention to visit halal destination in Lombok Island.…”
Section: Introductionmentioning
confidence: 95%
“…The relationship between social influence (similar to subjective norms) and the intention to continue using and to recommend certain products, services or technology is well established in the tourism, information technology and business literature. For example, [58], in their study that aimed to determine the effect of destination image and subjective norms on the intention to visit Lombok Island in Indonesia, found a significant relationship between social influence or subjective norms and tourists' intention to visit. In the context of sustainable rural tourism, ref.…”
Section: Relation Of Social Influence To Usage Continuance Intention ...mentioning
confidence: 99%
“…. Pulau Lombok juga pernah masuk dalam peringkat Destinasi Wisata Halal Terbaik di Indonesia menurut IMTI 2018 dan juga dinobatkan sebagai destinasi halal terbaik di kancah internasional bidang pariwisata (Ramadhani et al, 2020). Namun demikian, bencana alam gempa bumi Lombok 2018 dan pandemi Covid-19 tahun 2020 menyebabkan dampak bagi wisata Lombok.…”
Section: Intisari-pulau Lombok DI Indonesia Pernah Terpilih Sebagai Destinasi Wisata Halal Terbaik Dunia Dan Destinasi Bulan Madu Halal Tunclassified
“…Lombok was chosen as the World's Best Halal Tourism Destination and World's Best Halal Honeymoon Destination in the World Halal Tourism Summit in Dubai 2015 (Khoiriati et al, 2018). Lombok Island has also been ranked as the Best Halal Travel Destination in Indonesia according to IMTI 2018 and was also named the best halal destination in the international arena in tourism (Ramadhani et al, 2020). This is what motivates the provincial government to develop the tourism sector seriously with a focus on Halal tourism as a means to improve the local economy.…”
Section: Introductionmentioning
confidence: 99%